PEDV and BVDV coinfection activates the NF-κB pathway by a TLR7-dependent mechanism - Cheng, Jinghua; Li, Benqiang; Tao, Jie; Shi, Ying; Liu, Huili (Frontiers in Microbiology, 2025)
IntroductionIn recent years, coinfections of porcine epidemic diarrhea virus (PEDV) with other enteric pathogens have been frequently observed in diarrheal piglets. However, the underlying mechanisms of pathogen–pathogen or pathogen–host interactions during such coinfections remain to be elucidated.MethodsIn this study, an in vitro coinfection test of bovine viral diarrhea virus (BVDV) and PEDV was performed on model cells established before to explore the effect of coinfection on PEDV replication. Additionally, we used small interfering RNA (siRNA) assay to explore the role of TLRs related to NF-κB signaling in response to PEDV and BVDV coinfection.ResultsWe found that after preinfection with BVDV, PEDV replicates faster and more easily in PK15 cells. Further analysis revealed that coinfection of PEDV and BVDV significantly induced NF-κB activity, leading to increased translocation of the NF-κB p65 subunit from the cytoplasm to the nucleus. Moreover, TLR7 was identified as a key pattern recognition receptor in this process, mediating NF-κB activation and promoting the expression of inflammatory cytokines.DiscussionThese results suggest that synergistic interactions between PEDV and BVDV during coinfection may strongly activate the host immune system and enhance virus replication. This study provides new insights into the immune modulation mechanisms underlying viral coinfections.